Inflammatory response following in vitro exposure to methylmercury with and without n-3 long chain polyunsaturated fatty acids in peripheral blood mononuclear cells from systemic lupus erythematosus patients compared to healthy controls. (October 2018) - Crowe, William; Allsopp, Philip J.; Nyland, Jennifer F.; Magee, Pamela J.; Strain, J.J.; Doherty, Leanne C.; Watson, Gene E.; Ball, Elisabeth; Riddell, Claire; Armstrong, David J.; Penta, Kayla; Todd, Joshua J.; et al.
Abstract: Methylmercury (MeHg) is a proposed environmental stimulus in systemic lupus erythematosus (SLE). Humans are primarily exposed to MeHg through fish consumption. Fish are also important sources of n-3 long chain polyunsaturated fatty acids (n-3 LCPUFA). This in vitro study investigated the inflammatory response of isolated peripheral blood mononuclear cells (PBMCs), when exposed to either MeHg alone or with added n-3 LCPUFA, from SLE patients ( N  = 12) compared to healthy sex matched controls (N = 12). The PBMCs were isolated and exposed to 200 nM of MeHg for 24 h with or without pre-exposure to eicosapentaenoic acid (EPA) or docosahexaenoic acid (DHA) at a concentration of 100 μM each. Supernatants were analyzed for the inflammatory markers. Following exposure to MeHg, mean TNF-α concentrations were significantly higher in SLE patients (2226.01 ± 348.98pg/ml) compared to controls (701.40 ± 680.65 pg/ml) ( P  = .008). Pre-exposure of cells with MeHg and EPA resulted in a significantly higher concentration of IL-8 in supernatants from SLE patients (2137.83 ± 1559.01 pg/ml) compared to that of the controls (879.26 ± 979.49 pg/ml) ( P  = .030). EPA and DHA attenuated the pro-inflammatory inducing effects of MeHg in SLE and control cells. In summary, exposure to MeHg stimulated a higher TNF-α response in SLE patients compared with healthy controls; nevertheless the presence of n-3 LCPUFA reduced the overall inflammatory response, albeit to a lesser degree in SLE patients. Highlights: MeHg provokes a greater inflammatory effect in lupus patients than in controls. N-3 LCPUFA may mitigate the inflammatory inducing effects of MeHg. SLE patients should choose varieties of fish low in MeHg and high in n-3 LCPUFA